ANALISIS KINERJA TURBIN ANGIN DARRIEUS-H NACA 3412 DENGAN VARIASI JUMLAH BILAH DAN DIAMETER SUMBU PUTAR - Astuti, Fina Andika Frida; Fachrudin, Arif Rochman; Su'udy, Ahmad Hamim (Politeknik Negeri Semarang, 2021)
Wind energy is a renewable energy source that can be utilized by utilizing wind turbines which can convert wind energy into a form of mechanical energy and with a generator electrical energy can be generated. The purpose of this study was to analyze the performance of the Darrieus-H naca 3412 vertical axis wind turbine with variations in the number of blades, wind speed and diameter of the rotary axis. The method used in this research is to use an experimental method, namely by varying the diameter of the rotating axis, the number of blades and wind speed. The number of blades varied were 2, 3 and 4. The wind speeds that were varied were 3.2 m / s, 3.6 m / s, 4 m / s and 4.4 m / s. The diameter of the rotary axis used is 150 mm, 200 mm, 250 mm, 300mm and 350 mm. From the research, it is found that in all values of the diameter of the vertical axis wind turbine at a speed of 4 m / s, the more the number of blades will increase the output power of the wind turbine. The largest output power is on blade 4 with the largest diameter of the rotary axis, which is 3.52 WattsFor all wind speed values on a wind turbine with a number of blades of 4, the larger the diameter of the rotary axis will cause the greater the output power generated. The largest output power is 3.52, which is at the highest wind speed of 4 m / s, the largest diameter of the rotary axis, which is 350 mm. The greater the wind speed of all rotating axis diameters, the greater the output power produced, which is 3.5 W on the diameter of the rotary axis 4 with a wind speed of 4 m/s